A coping model for school psychological counsellors: A qualitative study - SEZGİN, OSMAN (My University, 2023)
This study analyzed the coping processes of psychological counsellors working in high schools in Turkey in the face of the challenges experienced in counselling sessions. The study used a qualitative research design: grounded theory. Semistructured interviews conducted with 33 high school counsellors were analyzed following Strauss and Corbin\"s analysis guidelines to create a coping model. The core category in the model was ‘coping’ while ‘actions/reactions’ explained what counsellors do to cope. Finally, ‘environmental factors’ and ‘personal factors’ influenced their coping processes. The findings are discussed in light of the existing literature to provide suggestions for school counsellors to develop self-care/coping strategies, increase their resilience and decrease their burnout.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Klinik Psikolojisi; Sağlık Bilimleri; Social Sciences and Humanities; Psychology; Clinical Psychology; Health Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Psikiyatri; PSİKOLOJİ, KLİNİK; PSİKOLOJİ, UYGULAMALI; Clinical Medicine (MED); Natural Sciences (SCI); PSYCHIATRY; PSYCHOLOGY; PSYCHOLOGY, CLINICAL; PSYCHOLOGY, APPLIED; Klinik Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; Uygulamalı Psikoloji; Psikiyatri ve Ruh Sağlığı; Social Sciences & Humanities; Applied Psychology; Psychiatry and Mental Health; coping model; grounded theory; qualitative research; school psychological counsellors; self-care; coping model; grounded theory; qualitative research; school psychological counsellors; self‐ care